Law in context - Bottomley, Stephen; Bronitt, Simon (Annandale, N.S.W. : Federation Press, 2012)
Law in Context exposes readers to the multitude of contexts (some explicit, others implicit) that affect how law is made, broken, and enforced by the state or individual citizens.--Back cover.
Includes bibliographical references and index.
Keywords: Law -- Australia -- Philosophy; Justice, Administration of -- Australia